Comparative-historical methods - Lange, Matthew (Los Angeles SAGE, 2013)
"This bright, engaging title provides a thorough and integrated review of comparative-historical methods. It sets out an intellectual history of comparative-historical analysis and presents the main methodological techniques employed by researchers, including: Comparative-historical analysis ; Case-based methods ; Comparative methods ; Data, case selection & theory. Matthew Lange has written a fresh, easy to follow introduction which showcases classic analyses, offers clear methodological examples and describes major methodological debates. It is a comprehensive, grounded book which understands the learning and research needs of students and researchers."--Publisher's website.
Comparative-Historical Methods: An Introduction -- An Intellectual History and Overview of Comparative-Historical Analysis -- The Within-Case Methods in Comparative-Historical Analysis -- Within-Case Methods and the Analysis of Temporality and Inter-Case Relations -- The Comparative Methods of Comparative-Historical Analysis -- Combining Comparative and Within-Case Methods for Comparative-Historical Analysis -- Data, Case Selection and Theory in Comparative-Historical Analysis -- Comparative-Historical Methods: Conclusion and Assessment.
Includes bibliographical references (pages 184-193) and index.
Keywords: Social sciences -- Research -- Methodology